Phylogeny and multiple independent whole‐genome duplication events in the Brassicales. Issue 8 (24th August 2020) - Mabry, Makenzie E.; Brose, Julia M.; Blischak, Paul D.; Sutherland, Brittany; Dismukes, Wade T.; Bottoms, Christopher A.; Edger, Patrick P.; Washburn, Jacob D.; An, Hong; Hall, Jocelyn C.; McKain, Michael R.; Al‐Shehbaz, Ihsan; et al.
Abstract : Premise: Whole‐genome duplications (WGDs) are prevalent throughout the evolutionary history of plants. For example, dozens of WGDs have been phylogenetically localized across the order Brassicales, specifically, within the family Brassicaceae. A WGD event has also been identified in the Cleomaceae, the sister family to Brassicaceae, yet its placement, as well as that of WGDs in other families in the order, remains unclear. Methods: Phylo‐transcriptomic data were generated and used to infer a nuclear phylogeny for 74 Brassicales taxa. Genome survey sequencing was also performed on 66 of those taxa to infer a chloroplast phylogeny. These phylogenies were used to assess and confirm relationships among the major families of the Brassicales and within Brassicaceae. Multiple WGD inference methods were then used to assess the placement of WGDs on the nuclear phylogeny. Results: Well‐supported chloroplast and nuclear phylogenies for the Brassicales and the putative placement of the Cleomaceae‐specific WGD event Th‐ɑ are presented. This work also provides evidence for previously hypothesized WGDs, including a well‐supported event shared by at least two members of the Resedaceae family, and a possible event within the Capparaceae. Conclusions: Phylogenetics and the placement of WGDs within highly polyploid lineages continues to be a major challenge. This study adds to the conversation on WGD inference difficulties by demonstrating that sampling is especially important for WGD identification and phylogenetic placement. Given its economic importance and genomic resources, the Brassicales continues to be an ideal group for assessing WGD inference methods.